Effects of Diboron Trioxide on Zinc Silicate-Based Glass-Ceramic Derived from Waste Soda Lime Silica for Potential Phosphor Materials Application - Alibe, I. M.; Nasir, S.; Zaid, M. H. M.; Alibe, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Over the last few decades, researchers have developed great deals of interest focusing on the fabrication and synthesis of zinc silicate-based glass-ceramic. However, using waste materials as precursors for the fabrication is yet another milestone in waste management. Thus, in this study, zinc silicate glass-ceramic was fabricated using sola lime silica (SLS) glass waste as a source of silicon. The series of precursor glass in the system was prepared by the conventional solid-state melt-quench technique through a controlled crystallization process. The physical, structural, and optical properties of the glass system were obtained by density measurement, X-Ray diffraction, Fourier Transform Infrared Spectroscopy, Ultraviolet-visible spectroscopy, respectively. The density of the glasses series was observed to be decreasing with the increment of content. The XRD spectra of the samples with 0 and 0.01 wt.% , exhibits major diffraction peaks attributed to the ZnO phase in the glass matrix. However, as content increased, the precursor glass sample shown by the XRD spectra depicted a broad halo characteristic, which reflected the properties of amorphous glass that were observed at the composition of 0.05 wt.% From FTIR spectra, the bands at 500, 688, 902 and 1243 can be associated with stretching vibrations of ZnO4 and Si-O-B bending vibrations, stretching vibration of the B–O bonds in the units, and modes of boron–oxygen triangular units. The intensity of the IR band increases with increasing percentage of . The UV-Vis analysis of the samples with 0 and 0.01 wt.% demonstrates crystalline hump and varies at 370 nm. It was observed that the addition of B2O3 to the ZnO-SLS glass network caused the glassy amorphous state with an absence of a sharp absorption edge at 0.05, 0.10, and 0.15 wt.% B2O3.The system shows increase in band gap when the composition of increased. When serves as a modifier, the number of NBOs will increase, and this will cause the expansion of glass network. The zinc silicate-based glass-ceramic produced has been classified to be a semiconductor due to the wide optical band gap energy obtained and may have key potential applications for future LED and other optoelectronic lighting devices.